Timing of Total Hip Arthroplasty Affects Lumbar Spinal Fusion Outcomes. Issue 2 (March 2022) - Mills, Emily S.; Bouz, Gabriel J.; Formanek, Blake G.; Chung, Brian C.; Wang, Jeffrey C.; Heckmann, Nathanael D.; Hah, Raymond J.
Abstract : Study Design: This is a retrospective cohort study of consecutive patients undergoing lumbar spinal fusion (LSF) within the PearlDiver Humana research database from 2010 to 2018. Objective: The aim of this study was to determine if timing of total hip arthroplasty (THA) affects LSF outcomes. Summary of Background Data: In patients with both spine and hip pathology, outcomes of THA have been shown to be affected by the timing of THA relative to LSF. However, few studies have assessed postoperative outcomes following LSF in this clinical scenario. Materials and Methods: A national database was queried for patients undergoing lumbar fusion and divided into 4 groups: (1) those who underwent LSF without THA (No THA); (2) those who underwent THA at least 2 years before LSF (>2 Prior THA); (3) those who underwent THA in the 2 years before LSF (0–2 Prior THA); and (4) those who underwent THA after LSF (THA After). We assessed lumbar-specific outcomes, including pseudarthrosis, revision, mechanical failure, and adjacent segment disease (ASD); as well as systemic complications. Controlling for age, sex, and Charlson comorbidity index, complication rates between all groups were assessed using univariate and multivariate logistic regression analysis. Post hoc comparisons were performed using the Fisher exact test with Bonferroni correction to account for multiple pairwise comparisons, resulting in an adjusted threshold for statistical significance of P <0.007. Results: When compared with the no THA group, those in the THA After group had a higher rate of ASD on multivariate analysis [adjusted odds ratio: 1.53, 95% confidence interval: 1.20–1.94, P <0.001]. When compared with all patients who underwent THA before LSF, patients who underwent THA after LSF had an increased risk of ASD (adjusted odds ratio: 3.80, 95% confidence interval: 2.21–6.98, P <0.001). Conclusions: Patients who undergo THA after LSF have an increased rate of lumbar-related complications both when compared with patients who do not undergo THA and when compared with patients who undergo THA before LSF.